(untitled) (JOURNAL OF ADVANCES IN MATHEMATICS, 2015)
In this paper, non linear finite fuzzy Volterra integral equation of the second kind is considered. The successive approximate method will be used t o solve it, and comparing with the exact solution and calculate the absolute error between exact and approximate method . Some numerical examples are prepared to show the efficiency and simplicity of the method.